Rheumatoid Factor, C-Reactive Protein, Erythrocyte Sedimentation Rate Responses on Brisk Walking in Rheumatoid Arthritis Women - Ali, Mohammad Arif; Kurniawati, Dewi Marfu'ah; Santillana, Leo Nacion; Guo, Ming Ming; Anam, Muhammad Saiful; Majid, Muhammad Faisal; Anggita, Gustiana Mega; Agustina, Azkia (Jurnal Kesehatan Masyarakat, 2024)
Modified Physical Exercise Program (MPEP) is necessary for people with rheumatoid arthritis (RA). This study aims to investigate the effects of MPEP on the Rheumatoid Factor (RF), C-Reactive Protein (CRP), and Erythrocyte Sedimentation Rate (ESR); to evaluate the correlation between CRP-ESR. This is a quasi-experimental study. Ten RA women who were recommended by the Dukuhseti PHC have participated. The procedure is ethically approved. The venous blood samples were used to measure the dependent variables. Eight-teen sessions of MPEP were done. A two-tailed paired t-test to elucidate the differences in pre-post data; the bivariate Pearson correlation test for CRP-ESR. The RF increased significantly (pre: 19,40±2,46 and post: 22,40±2,41). CRP increased (pre: 0,30±0,07 and post: 0,37±0,06; p 0,05). The change in ESR is not significant. There is a strong-positive, significant correlation (r: 0,831) between CRP-ESR. We concluded that MPEP is not able to lower the RA parameters, and there is a positive feedback correlation between CRP-ESR.